ZnO nanowire biosensors for detection of biomolecular interactions in enhancement mode - Choi, Ahmi; Kim, Kyoungwon; Jung, Hyo-Il; Lee, Sang Yeol (ELSEVIER SCIENCE SA, 2010)
One-dimensional oxide semiconductors have two main advantages for use in biosensors: oxide stable surfaces and high surface-to-volume ratios. In this paper, we describe a ZnO nanowire (NW) field effect transistor (FET) based biosensor for the detection of low level biomolecular interactions. ZnO NWs were grown on Au-coated Al2O3 (0 0 0 1) substrates by using pulsed laser (PL) deposition in an alumina tube placed inside a furnace. Field emission scanning electron microscopy (FE-SEM) images indicate that the average diameters of the ZnO NWs were about 70 nm, and that the average length was about 8 mu m. The well-crystallized structural quality of the ZnO NW was examined using photoluminescence (PL) emission measurement. The ZnO NW biosensor functionalized with biotin can easily detect streptavidin binding. The binding of streptavidin with the concentrations from 0 to 250 nM resulted in the electrical current changes of up to 22.5 nA. The ZnO NW biosensor could detect as low as 2.5 nM of the streptavidin with 7.5 nA of current increase, which implied that the sensitivity of the biosensor can be below the nM concentration of biomolecules. This novel ZnO NW biosensor has potential for sensitive, label-free, and real time detection of a wide range of biological species. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ZINC-OXIDE; FABRICATION; DEPOSITION; GREEN